Ashobiyah dan Mulk: Menerapkan Theory Ibn Khaldun Ke Dalam Sejarah Empiris Gerakan Dakwah Islam Di Periode Kerajaan Demak - UI Ardaninggar Luhtitianti; Achmad Zainal Arifin (Religia, 2021)
Ashabiyah and Mulk are positioned as a driving force in the big frame of Ibn Khaldun’s theory about the Rise and Fall of Dynasty. Although many studies on Ashabiyah and Mulk have been carried out, there have been very few attempts to apply them into the empirical phenomena in various society. This paper intends to apply Ashabiyah and Mulk’s theory of Ibn Khaldun in the history of the role of saints’ da’wa and their alliances with the rulers in the period of Demak’s Empire. The research was compiled using literature studies, with the main source of Muqaddimah and various related research articles. The analysis results show that Ibn Khaldun’s theory is suitable for explaining the essence of the end of Demak's Empire, namely the weakening of the Ashabiyah. Furthermore, Ashabiyah and Mulk are proven to be still relevant in analyzing the socio-religious phenomenon both in the empirical history and in the contemporary muslim’s society.